Mimicking Multiple Myeloma: The Importance of the Differential Diagnosis - Derudas, Daniele; Concu, Claudia; Durzu, Tania; Piras, Doloretta; Nemolato, Sonia; Liguori, Anna Maria; Simula, Maria Pina; Nasa, Giorgio La (Archives of Clinical and Medical Case Reports, 2024)
Multiple myeloma (MM) is a malignant disease of plasma cells that accounts for 15% of hematologic malignancies. Clinical manifestation is defined by the presence of anemia, renal failure, hypercalcemia, and osteolytic bone lesions, referred to by the acronym CRAB. Here, we describe the case of a Caucasian male who was referred to our center because of a clinical suspicion of MM. A comprehensive workup, including blood tests, radiologic studies, and a bone marrow biopsy, ruled out the presence of plasma cell neoplasia. Further investigations, such as the CT guided biopsy of a lytic lesion, allowed us to diagnose a brown tumor (BT), a tumor-like lesion resulting from the bone remodeling process associated with persistent hyperparathyroidism. This diagnosis was confirmed by endocrinological investigations, followed by parotidectomy, during which the clinical manifestations disappeared. Our case illustrates the importance of an accurate differential diagnosis when MM is suspected, as the simultaneous presence of comorbidities and diseases can confuse the evaluation. In particular, the combination of anemia, peripheral neuropathies, and renal dysfunction could be associated with a number of other causes, and it is imperative to perform a thorough history, clinical and instrumental examination, and laboratory tests to rule out other etiologies.